2019
DOI: 10.1093/asj/sjz112
|View full text |Cite
|
Sign up to set email alerts
|

Fat Extract Improves Random Pattern Skin Flap Survival in a Rat Model

Abstract: Background Adipose tissue and its derivatives, including adipose-derived stem cells, stromal vascular fraction (SVF), and SVF-gel, have been utilized in the treatment of many ischemic disorders. However, the utilization of these products is limited in clinical applications by concerns related to the presence of cells in these derivatives. Objectives This study aimed to isolate a cell-free fat extract (FE) from fat tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The concentration of the CEFFE was approximately 5 ug/ul, which contained 2 pg/ul of BDNF. As we have shown, CEFFE contains diverse neurotrophic factors [8,15] and may promote axon regeneration that is more robust than that promoted by the use of a single neurotrophic factor; this nding is consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The concentration of the CEFFE was approximately 5 ug/ul, which contained 2 pg/ul of BDNF. As we have shown, CEFFE contains diverse neurotrophic factors [8,15] and may promote axon regeneration that is more robust than that promoted by the use of a single neurotrophic factor; this nding is consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Given our previous ndings on CEFFE's positive effects on wound healing, [8][9][10][11]15] we examined its effects on injured CNS repair. In the present study, we demonstrated that CEFFE has neuroprotective and axon regenerating effects on injured RGCs, which suggest its potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…with 250 μl of PBS as vehicle (TS + vehicle), and a tail-suspended group that was injected i.p. with 250 μl [the administration dose of CEFFE was referred to our previous published article (Cai et al, 2019)] of CEFFE (TS + CEFFE) twice a week for 4 weeks after suspension for 3 weeks, and the mice were still in tail suspension during the administration period. The extraction of CEFFE was performed as described previously (Yu et al, 2018).…”
Section: Ceffe Preparationmentioning
confidence: 99%
“…Furthermore, CEFFE is a cell-free liquid that greatly reduces its immunogenicity and ensures its safety during treatment. Our previous studies have found it to have proangiogenic activity (Yu et al, 2018) and found that it improved skin flap survival (Cai et al, 2019), improved fat graft survival (Zheng et al, 2019), and promoted the healing of diabetic wounds (Wang et al, 2020;Yin et al, 2020). CEFFE contains cytokines and growth factors such as IGF1, bFGF, and other growth factors, which can promote bone growth (Pedersen and Febbraio, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al have observed the effect of ATE on adipose tissue regeneration in an engineering chamber model, in which regenerated adipose tissue of ATE group exhibited more considerable volume, better morphology and structure, a thinner capsule, and more vessels compared with control group [ 39 ]. Cai et al revealed that ATE (named as fat extract in their research) isolated from human fat contained proangiogenic growth factors that promoted proliferation, migration, and tube formation in HUVEC in vitro, while the treatment of ATE increased capillary density of skin flap, thereby reducing flap necrosis in a rat model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%